La Münchener Rück fait le point sur l’assurance spatiale - collaborateurs de la compagnie Munich Reinsurance, Divers (Assurances)

(untitled) (HEC Montréal, 1992)
On occasion of International Space Year 1992, various collaborators from Munich Reinsurance, the world's largest reinsurer, review the development of space insurance from its early days to today. ln the field of space insurance, where even a minor technical breakdown can mean the total loss of a rocket, the satellite or both, accumulated losses from 1965 to 1991 have nearly exceeded the accumulated premiums. Covering such delicate risks for sums which currently exceed U.S. $250 million for property loss and twofold this amount for liability, can only be possible through an international reinsurance network. Moreover, space insurance can only be practiced in conjunction with a long-term underwriting policy. Before posting a profit, insurers must be prepared to expose themselves to significant losses over a number of years. After twenty-five years, overall market results are not very satisfactory. Reinsurers today are concerned with the continuing decline in rates which began some time ago. If this trend continues, the market will once again begin to experience extremely negative results.